Quo Vadis Kebijakan Pemerintah Terhadap Legalitas Keberadaan Investasi Robot Trading (Expert Advisor) dikaji menggunakan Teori Hukum dan Pembangunan - Tungmiharja, Wilson; Gultom, Elfrida Ratnawati (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
The purpose of writing this journal is to analyze and understand government policies regarding the legality of trading robots. The development of the times has provided many advances in both the technological and economic fields, technological advances have provided openness to trade in both goods and services. Forex trading is a business activity that offers high profits accompanied by high risks, where individuals must monitor and study the movements of the money market without stopping to make transactions. The existence of trading robots makes it easy to do forex trading due to automation to save time and does not require in-depth understanding of forex trading. The existence of trading robots provides an opportunity for criminal acts to occur in the forex field, one of which is the existence of Illegal Trading Robots which results in losses for users. One of them is the fraudulent investment case of Net 89, which has a trading robot mode, which uses a permit to sell e-books in carrying out trading activities based on trading robots. This problem has resulted in an urgency that can be seen from the enactment of BAPPEBTI Regulation Number 12 of 2022 as a step to regulate the existence of trading robots.